Constribuições dos métodos simplex e das resoluções gráficas à aprendizagem da álgebra linear no Ensino Médio - Vasconcelos, Eduardo Silva (2013)
This paper aims to describe the Simplex Method and Method of Resolution Graphics problems on Linear Programming, aiming at the teaching and learning of linear algebra in high school. And for this, presents some basic concepts in linear programming, it follows brie y on the Simplex Method and Method of Resolution Graphics and presents two resolutions of Linear Programming problems, a maximization and minimization another, both problems are solved by two methods cited. We understand the importance of this work is to present the Simplex Method eao Method Graphical resolution to high school students because we believe that together these two methods applied in teaching linear algebra could lead to increased motivation of students in learning mathematics.